Late postoperative complications in surgical patients: an integrative review - Álvaro Francisco Lopes de Sousa; Lucas Lazarini Bim; Paula Regina de Souza Hermann; Inês Fronteira; Denise de Andrade (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to identify the main complications in the late postoperative period of surgical patients. Method: an integrative review from the CINAHL, LILACS, Science direct, Web of Science, SCOPUS, Europe PMC, and MEDLINE databases. Descriptors and keywords were combined without language or time restriction. Results: ten primary studies were included. Infectious complications were the most common, especially surgical site infection, pneumonia and urinary tract infection. The presence of complications was linked to increased mortality, need for reoperations and worse survival. Few studies report on monitoring frequency, follow-up time and/or when complications started to be observed. Conclusion: infectious complications were the most prevalent postoperatively. The scarcity of guidelines that guide the monitoring of complications regarding monitoring frequency, follow-up time and classification makes it difficult to establish an overview of them and consequently propose intervention strategies.